Depositional and diagenetic constraints on the quality of shale‐gas reservoirs: A case study from the Late Palaeocene of the Potwar Basin (Pakistan, Eastern Tethys). Issue 7 (15th March 2022) - Khan, Nasar; Weltje, Gert Jan; Jan, Irfan U.; Swennen, Rudy
Abstract : Unconventional shale‐gas reservoir assessment concurs numerous exploration challenges, often related to their complex lithology, which reflects secular changes in depositional environment(s) as well as spatially variable diagenetic overprinting. This study combines a range of methods (sedimentological, petrographical, CL‐microscopy, X‐ray diffraction, TOC (total organic carbon), TON (total organic nitrogen) and δ 13 Corg and δ 15 Norg stable isotopes) to address the controls of lithofacies, palaeo‐depositional environment(s) and diagenesis on the shale‐gas reservoir potential of the Late Palaeocene Patala Formation in the Potwar Basin of Pakistan. This formation records sediment accumulation in a shallow, mixed siliciclastic‐carbonate shelf environment. Sedimentological and X‐ray diffraction (XRD) analyses show that the formation is primarily composed of an alternation of carbonaceous, siliceous, calcareous and argillaceous mudstone lithofacies. Detrital assemblages, including grains of quartz, apatite, calcite, chlorite, as well as organic matter (OM) and clay minerals with auxiliary (authigenic) pyrite, dominate the formation. High terrigenous influx is represented by the abundance of siliciclastics and terrigenous OM. The δ 13 Corg and δ 15 Norg proxies reflect dysoxic to anoxic palaeo‐environmental conditions, which promoted preservation of mixed marine and terrigenous OM, a setting considered to be indicative for high shale‐gas potential. The organic‐rich siliceous and carbonaceous mudstone lithofacies are considered to be the most prospective intervals, while calcareous and argillaceous mudstones are considered least promising in terms of reservoir quality. Spatially variable eo‐, meso‐ and telo‐diagenetic features such as compaction, cementation, stylolitization, dissolution and re‐precipitation are superimposed upon the depositional fabric, which locally affected the reservoir quality of the Patala Formation. The results of this study strongly suggest that the organic‐ and quartz‐rich mudstone lithofacies constitute "sweet spots" whose occurrence in space and time may be traced to design a strategy for shale‐gas exploration in the Potwar Basin of Pakistan and in analogous settings elsewhere. Abstract : Unconventional shale‐gas reservoir quality of the Patala Formation is constrained by lithofacies characteristics, palaeo‐depositional environment(s) and diagenetic evolution in the Potwar Basin of Pakistan. Organic enrichment and mineralogical composition of the lithofacies also influenced the shale‐gas reservoir potential of the formation.